SGLT2抑制剂对糖尿病肾病患者的影响:基于尿足细胞的初步研究 - Emre Durcan; Serbay Ozkan; Halil Ibrahim Saygi; Mevlut Tamer Dincer; Ozge Polat Korkmaz; Serdar Sahin; Cebrail Karaca; Cem Sulu; Alev Bakir; Hande Mefkure Ozkaya; Sinan Trabulus; Elif Guzel; et al. (Journal of Diabetes, 2022)
Abstract Background The aim of this study was to investigate the effects of sodium glucose cotransporter 2 inhibitors (SGLT2i) on the glomerulus through the evaluation of podocyturia in patients with diabetic kidney disease (DKD). Methods The study population was composed of 40 male patients with type 2 diabetes mellitus; 22 of them received SGLT2i (SGLT2i group), and the others who did not were the control. The DKD‐related parameters of patients were monitored before SGLT2i initiation, and then in the third and sixth month of the follow‐up period. Patients' demographic, clinical, laboratory, and follow‐up data were obtained from medical charts. Microalbuminuria was measured in 24‐h urine. The number of podocytes in the urine was determined by immunocytochemical staining of two different markers, namely podocalyxin (podx) and synaptopodin (synpo). Concentrations of urine stromal cell‐derived factor 1a and vascular endothelial growth factor cytokines were quantified with an enzyme‐linked immunosorbent assay kit. Results At the end of the follow‐up period, decreases in glycosylated hemoglobin, glucose, systolic and diastolic blood pressure, uric acid level, and microalbuminuria, and improvement in body mass index level and weight loss were significant for the SGLT2i group. On the other hand, there was no significant difference in terms of these parameters in the control group. The excretion of synaptopodin‐positive (synpo+) and podocalyxin‐positive (podx+) cells was significantly reduced at the end of the follow‐up period for the SGLT2i group, while there was no significant change for the control. Conclusions At the end of the follow‐up period, male patients receiving SGLT2i had better DKD‐related parameters and podocyturia levels compared to baseline and the control group. Our data support the notion that SGLT2i might have structural benefits for glomerular health.